The Road to Rural Revitalization by Combining Green Finance with Red Tourism Taking Jinzhai as an Example - Lv, Jiaqi; Li, Deyu (International Journal of Global Economics and Management, 2024)
This article takes Jinzhai County as an example to explore the path of rural revitalization by combining green finance with red tourism. Firstly, the rich red tourism resources and green ecological environment in Jinzhai County were analyzed, and the necessity of combining green finance with red tourism was proposed. Subsequently, the green finance policies and their implementation in Jinzhai County were sorted out, and the support for the development of red tourism was evaluated. Then, the article explores the specific models and paths of combining green finance with red tourism, and proposes strategies and suggestions for rural revitalization in Jinzhai County. Finally, the successful experience of Jinzhai County in combining green finance and red tourism was summarized through case analysis, providing reference for rural revitalization in other regions.